East Asian Uses of Indian Epic Literature: Refractions of the Mahabharata in Japan and China, Late Nineteenth–Early Twentieth Century - Bender De Moniz Bandeira, Egas Bernard (The Mahabharata in Global Political and Social Thought, 2024)
Introduction In 1909, the Sino-Japanese poet Su Manshu painted an image of Cai Yan (Lady Wenji), a poetess of the late second century who had spent 12 years in captivity abroad before returning to the Han Empire, and sent it to his friend, the art collector Liu Jiping (also known as Liu San). Liu wrote a series of poems to appreciate Su's gift, including the following verses: Why would a Chinese literatus at the turn of the twentieth century write a poem mentioning the Indian epic Mahabharata to match a seemingly unrelated painting? Until well into the twentieth century, the name of the Mahabharata had been mostly unknown in East Asia, except for a few isolated references in Buddhist texts. Against the sheer preponderance of Buddhist thought in the intellectual flows between India and China, it might even have seemed futile to look for an East Asian reception of the Mahabharata. Yet, over the centuries, various elements related to the Mahabharata circulated between South Asia and East Asia and played significant roles within East Asian culture itself. By the late nineteenth and early twentieth centuries, Indian thought continued to play a major role in East Asia amidst intense contact between China, Japan, Europe, and India itself. In close interdependence with the notion of the ‘West’, the category of ‘Asia’ emerged in the Japanese and Chinese imaginary by the turn of the twentieth century, when intellectuals developed a globalized sense of their position in the world. India became a renewed object of study but, at the same time, also a ‘method’ to deal with the challenges posed by modernity. Interest in India and its role within ‘Asia’ was a significant element not only in understanding the geopolitical realities and ‘catching up’ with the ‘West,’ but also in the quest for a ‘world beyond the material and epistemological constraints’ posed by Western modernity. While Buddhism still played a crucial role as the connecting bond between the two macroregions of East Asia and South Asia, some intellectuals came to understand it in a wider framework that also encompassed other traditions such as that of the Mahabharat